Relationship between isokinetic strength and field tests of physical fitness in elite junior tennis players - Roetert, E. P.; McCormick, T. J.; Brown, S. W.; Ellenbecker, T. S. (Medicine & Science in Sports & Exercise, 1996)
Isokinetic trunk strength, as measured on a Cybex dynamometer, and various standard field tests for strength, power, speed, agility, endurance, and flexibility were evaluated in relation to measures of muscular speed and power in 60 nationally-ranked junior tennis players. The isokinetic measures were related to the speed and power tests (e.g., grip strength, vertical jump, spider agility run, and lateral shuffle) but not to tests such as number of sit-ups, push-ups in one minute, and 1.5 mile run. This indicates that isokinetic testing is a better indicator of speed and power in tennis players than the muscular endurance tests used in the study. That result was obtained despite the isokinetic and sit-up tests using the same muscle groups. It was suggested that a form of specificity might be developed through tennis playing in these athletes which is only measured by the isokinetic test. Implication: Only a subset of fitness tests were significantly related in junior tennis players indicating that not every fitness test will reveal important information about tennis fitness.